Clinical physiological basis for application of means of physical rehabilitation in surgical diseases - Manshulovsky V.M; Mohammed Ali (Kharkov National Pedagogical University, 2011)
Opinions concerning complications after surgical operations of abdominal viscera of patients are considered. The analysis of publication of various authors about the reasons of complications after surgical operations is carried out. The opinion that the most important reason of postoperative complication is a hypokinesia of patients in the postoperative period is advanced. It is shown that the hypokinesis is the factor which begins pathophysiological changes in an organism of the patient coming to an end with postoperative complications. It is offered to include physiotherapy exercises, massage and physiotherapeutic procedures in medical complexes as means of physical rehabilitation for preventive maintenance of postoperative complications as patients after surgical operation.